How Inuit in the Canadian North Perceive the Wolverine: From Past to Present - Frédéric Laugrand (Études Inuit Studies, 2019)
The wolverine is an animal perceived by the Inuit in northern Canada as a voracious and powerful creature. Often associated with the wolf, it occupies a singular place in the bestiary of these peoples. The wolverine is a predator, a nomad, a scavenger; but it is also a thief, capable of endangering the humans it follows by destroying their meat caches. A sly trickster, the animal’s cunning and determination make it a formidable adversary for other animals and humans alike. While these characteristics have earned the wolverine a bad name in everyday life, they have also contributed to its status as a powerful tuurngaq, an auxiliary spirit, in the shamanic world. The wolverine is an ambivalent being that arouses fear and dread among hunters. Le carcajou ou glouton est un animal que les Inuit du Nord canadien perçoivent comme un être vorace et puissant. Souvent associé au loup, il occupe une place singulière dans le bestiaire de ces peuples. Prédateur, nomade, il est aussi charognard mais surtout voleur, capable de mettre en péril les humains qu’il suit et dont il détruit les caches à viande. Fourbe à l’image des « tricksters », sa ruse et sa détermination en font un adversaire redoutable pour les animaux comme pour les humains. Toutes ces caractéristiques lui donnent mauvaise réputation dans la vie quotidienne mais le prédestinent à devenir un puissant tuurngaq, un esprit auxiliaire, dans le domaine chamanique. Le carcajou est ainsi un être ambivalent qui suscite la crainte et la hantise des chasseurs.